The associations between asthma and common comorbidities: a comprehensive Mendelian randomization study - Wang, Xuezhao; Huang, Yuchen; Li, Xiaochen; He, Yuanzhou; Liu, Xiansheng (Frontiers in Medicine, 2023)
Background Asthma is a chronic respiratory disease and is often associated with multiple comorbidities. The causal relationship between asthma and these comorbidities is still unclear. This study aimed to investigate the association between genetically predicted asthma and common comorbidities. Methods After searching PubMed and GWAS summary statistics, we identified 26 comorbidities of asthma. The causal relationship between asthma and comorbidities was assessed in two independent GWASs by bidirectional Mendelian randomization, followed by validation of the results using a multivariate Mendelian randomization analysis and several sensitivity analyses. Results In the bidirectional Mendelian randomization analysis, chronic sinusitis [odds ratio (OR) = 1.54, p = 1.40 × 10−5], atopic dermatitis (OR = 1.36, p = 9.37 × 10−21), allergic conjunctivitis (OR = 2.07, p = 4.32 × 10−6), and allergic rhinitis (OR = 1.53, p = 5.20 × 10−6) were significantly associated with increased asthma risk. Hyperthyroidism (OR = 1.12, p = 0.04) had a potential increased risk for asthma. For the reverse direction, asthma showed significant associations with an increased risk of chronic obstructive pulmonary disease (OR = 1.24, p = 2.25 × 10−9), chronic sinusitis (OR = 1.61, p = 5.25 × 10−21), atopic dermatitis (OR = 2.11, p = 1.24 × 10−24), allergic conjunctivitis (OR = 1.65, p = 6.66 × 10−35), allergic rhinitis (OR = 1.90, p = 2.38 × 10−57), and a potential higher risk of allergic urticaria (OR = 1.25, p = 0.003). Conclusion This study suggested a significant bidirectional association of chronic sinusitis, atopic dermatitis, allergic conjunctivitis, and allergic rhinitis with asthma. In addition, hyperthyroidism was associated with an increased risk of asthma and asthma increased the risk of chronic obstructive pulmonary disease and allergic urticaria.